Contributions to the morphology and histology of the nudibranch Melibe rosea (Rang) - De Vries, J. B (Stellenbosch : Stellenbosch University, 2012)
The morphology and histology of the alimentary canal, and the circulatory, excretory, reproductive and nervous systems are described.